2012
DOI: 10.1155/2012/459278
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Activates TGF-Beta but Inhibits BMP Receptor-Mediated Smad Signaling and Smad4 Binding to Hepcidin Promoter in the Liver

Abstract: Hepcidin, a key regulator of iron metabolism, is activated by bone morphogenetic proteins (BMPs). Mice pair-fed with regular and ethanol-containing L. De Carli diets were employed to study the effect of alcohol on BMP signaling and hepcidin transcription in the liver. Alcohol induced steatosis and TGF-beta expression. Liver BMP2, but not BMP4 or BMP6, expression was significantly elevated. Despite increased BMP expression, the BMP receptor, and transcription factors, Smad1 and Smad5, were not activated. In con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 58 publications
1
34
0
Order By: Relevance
“…As described in the introduction section, expression of BMP2 and BMP4 has been reported in acute liver injury 6. Furthermore, BMP2, but not BMP4 or BMP6, expression was found to be significantly elevated in a model of chronic alcohol feeding in mice 31. Together, these data indicate that increased hepatic BMP6 expression in NAFLD results from hepatocellular lipid accumulation independent of liver inflammation and injury.…”
Section: Resultsmentioning
confidence: 66%
“…As described in the introduction section, expression of BMP2 and BMP4 has been reported in acute liver injury 6. Furthermore, BMP2, but not BMP4 or BMP6, expression was found to be significantly elevated in a model of chronic alcohol feeding in mice 31. Together, these data indicate that increased hepatic BMP6 expression in NAFLD results from hepatocellular lipid accumulation independent of liver inflammation and injury.…”
Section: Resultsmentioning
confidence: 66%
“…Following an insult, TGF-Ī² can reduce production of pro-inflammatory cytokines such as IL-2 and proliferation of T helper immune cells (Su et al, 2012). TGF-Ī² is increased in the liver during alcohol-induced hepatic disease (Meyer et al, 2010; Gerjevic et al, 2012), but its role in the brainā€™s response to alcohol exposure has yet to be fully investigated. Recent work from the Valenzeula group (Topper et al, 2015) found no changes to TGF-Ī² in the hippocampus and cerebellum of rats exposed to alcohol vapor during the neonatal period, possibly indicating an influence of route of administration or timing of analysis on the anti-inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…TGFĪ² signaling is inhibited by ethanol in rat cerebral cortex [154]. However, TGFĪ² is activated by ethanol in mouse liver and rat alveolar macrophage [155,156]. Meanwhile, exposure to ethanol increases fibroblast contraction, which is reduced by TGFĪ² inhibition [157].…”
Section: Disturbance Of Signaling Pathways In Squamous Epithelial mentioning
confidence: 99%